A note on liquidity policies and financial networks. Issue 3 (5th August 2019) - Lopomo Beteto Wegner, Danilo
Abstract : Purpose: This paper aims to provides an example of how government and central bank policies that promote market liquidity (e.g., quantitative easing programs) can change the structure of the banking system. Design/methodology/approach: The nexus between liquidity policies and financial networks is addressed through an example that captures stylized features of the interbank market. In the example discussed, two scenarios are considered: one with and another without central bank/government liquidity provision, leading to two different network structures that are then used to study the likelihood of contagion. Findings: The example provided shows that government and central bank policies that promote market liquidity can lead to financial networks that are better capitalized (net worth of the banking system is higher) but, at the same time, more fragile (higher likelihood of bank failures). Originality/value: To the best of the author's knowledge, this is the first attempt to model the formation of a financial network with an explicit mechanism accounting for government and central bank policies that affect market liquidity, which, in turn, could be interpreted as a quantitative easing program.